Normal distribution of H3K9me3 occupancy co-mediated by histone methyltransferase BcDIM5 and histone deacetylase BcHda1 maintains stable ABA synthesis in Botrytis cinerea TB-31 - Wei, Zhao; Shu, Dan; Hou, Xiaonan; Li, Tianfu; Li, Zhemin; Luo, Di; Yang, Jie; Tan, Hong (Frontiers in Microbiology, 2024)
Abscisic acid (ABA) is a conserved and important "sesquiterpene signaling molecule" widely distributed in different organisms with unique biological functions. ABA coordinates reciprocity and competition between microorganisms and their hosts. In addition, ABA also regulates immune and stress responses in plants and animals. Therefore, ABA has a wide range of applications in agriculture, medicine and related fields. The plant pathogenic ascomycete B. cinerea has been extensively studied as a model strain for ABA production. Nevertheless, there is a relative dearth of research regarding the regulatory mechanism governing ABA biosynthesis in B. cinerea. Here, we discovered that H3K9 methyltransferase BcDIM5 is physically associated with the H3K14 deacetylase BcHda1. Deletion of Bcdim5 and Bchda1 in the high ABA-producing B. cinerea TB-31 led to severe impairment of ABA synthesis. The combined analysis of RNA-seq and ChIP-seq has revealed that the absence of BcDIM5 and BcHda1 has resulted in significant global deficiencies in the normal distribution and level of H3K9me3 modification. In addition, we found that the cause of the decreased ABA production in the ΔBcdim5 and ΔBchda1 mutants was due to cluster gene repression caused by the emergence of hyper-H3K9me3 in the ABA gene cluster. We concluded that the ABA gene cluster is co-regulated by BcDIM5 and BcHda1, which are essential for the normal distribution of the B. cinerea TB-31 ABA gene cluster H3K9me3. This work expands our understanding of the complex regulatory network of ABA biosynthesis and provides a theoretical basis for genetic improvement of high-yielding ABA strains.